2013
DOI: 10.1371/journal.pone.0074381
|View full text |Cite
|
Sign up to set email alerts
|

Increased Endoplasmic Reticulum Stress Response Is Involved in Clopidogrel-Induced Apoptosis of Gastric Epithelial Cells

Abstract: BackgroundThe widespread use of clopidogrel alone or in combination with aspirin may result in gastrointestinal mucosal injury, clinically represented as recurrent ulceration and bleeding complications. Our recent work suggested that clopidogrel significantly induced human gastric epithelial cell (GES-1) apoptosis and disrupted gastric mucosal barrier, and that a p38 MAPK inhibitor could attenuate such injury. However, their exact mechanisms are largely unknown.MethodsThe GES-1 cells were used as a model syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…A possible explanation is that ticagrelor activates the mitogen-activated protein kinase (MAPK) pathway. Studies on gastric epithelial cells have shown that clopidogrel—another P2Y12 antagonist—induces ER stress through activation of p38-MAPK [ 39 ]. In addition, the P2Y12 receptor has been shown to act on the MAPK pathway in microglial cells during nerve injury [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that ticagrelor activates the mitogen-activated protein kinase (MAPK) pathway. Studies on gastric epithelial cells have shown that clopidogrel—another P2Y12 antagonist—induces ER stress through activation of p38-MAPK [ 39 ]. In addition, the P2Y12 receptor has been shown to act on the MAPK pathway in microglial cells during nerve injury [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…When a large number of unfolded or misfolded proteins accumulate in the endoplasmic reticulum, the normal physiological function will be changed. This phenomenon is known as ERS 36,37 . ERS primarily acts through activating IRE-1, which is a significant event in andrographolide-induced CRC cell death 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The human embryonic kidney cell line HEK293 was purchased from the Microbix Biosystems (Ontario, Canada). The human gastric mucosa epithelial cell line GES-1 was kindly gifted by the Nanjing First Hospital, Nanjing Medical University (Nanjing, China) [30, 31]. The cells were cultured at 37°C and 5% CO 2 in Dulbecco's modified Eagle's medium (DMEM) with 10% fetal bovine serum (FBS), 10 U/mL penicillin and 10 U/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%